MYOCARDIAL INFARCTION DIAGNOSIS USING FUZZY-EXPERT APPROACH (Journal of Information and Communication Technology, 2004)
A fuzzy expert system is a system which incorporates fuzzy sets and/or fuzzy logic into its reasoning process and/ or knowledge representation scheme. It allows the knowledge to be encoded in a form that reflects the way experts think about a complex problem. Since fuzzy expert approach model imprecise information, it improves the cognitive modelling of the problem and therefore makes it more powerful. The Expert system and fuzzy logic have their own significant capabilities; hence the combination of both technologies that form a fuzzy-expert system or a hybrid system could increase the systems performance (Herrmann, 1996). This paper presents the use of such technologies in the system known as FEMInS. The system assists the general medical practitioners in handling heart attack cases that have been referred to them. Unlike conventional expert systems, FEMIns implemented the fuzzy logic technique in its inference engine. Since fuzzy logic can be used for prediction, and expert system can provide explanation and reasoning, the combination of both fields is able to cope with the problems of uncertainty and provide the explanation of the results to the user. FEMIns demonstrates that both fuzzy logic and expert system complement rather than complete with each other.